2010
DOI: 10.1073/pnas.1002175107
|View full text |Cite
|
Sign up to set email alerts
|

A minority of foci or pan-nuclear apoptotic staining of γH2AX in the S phase after UV damage contain DNA double-strand breaks

Abstract: UV irradiation induces histone variant H2AX phosphorylated on serine 139 (γH2AX) foci and high levels of pan-nuclear γH2AX staining without foci, but the significance of this finding is still uncertain. We examined the formation of γH2AX and 53BP1 that coincide at sites of double-strand breaks (DSBs) after ionizing radiation. We compared UV irradiation and treatment with etoposide, an agent that causes DSBs during DNA replication. We found that during DNA replication, UV irradiation induced at least three clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
185
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(215 citation statements)
references
References 41 publications
29
185
1
Order By: Relevance
“…S1D), similar to what had been observed following exposure to bleomycin. Unlike cells showing clear repair foci, where γH2AX and 53BP1 mostly colocalize, 53BP1 did not stain in γH2AX pan-stained cells, which is consistent with previous observations (30,32,33). For serotypes 19F and 3, there was a greater frequency of γH2AX-positive cells compared with uninfected cells, although the ability of these serotypes to induce DSB foci was clearly reduced compared with serotype 4 (Fig.…”
Section: S Pneumoniae Induces Dna Damage Responses In Alveolar Epithsupporting
confidence: 91%
“…S1D), similar to what had been observed following exposure to bleomycin. Unlike cells showing clear repair foci, where γH2AX and 53BP1 mostly colocalize, 53BP1 did not stain in γH2AX pan-stained cells, which is consistent with previous observations (30,32,33). For serotypes 19F and 3, there was a greater frequency of γH2AX-positive cells compared with uninfected cells, although the ability of these serotypes to induce DSB foci was clearly reduced compared with serotype 4 (Fig.…”
Section: S Pneumoniae Induces Dna Damage Responses In Alveolar Epithsupporting
confidence: 91%
“…8C). Because ␥H2AX is accumulated at the site DNA damages, including DSB and ICL, which cause stalling of replication fork, 53BP1 protein is mainly enriched at sites of DSB (39). Therefore, the PN staining of ␥H2AX without 53BP1 focus observed in the present study is suggested to represent replication fork stalling caused by ICL rather than DSB.…”
Section: Analysis Of ␥H2ax and 53bp1 Localization In Response To Icl mentioning
confidence: 53%
“…Our data show that the lack of REV7 function results in accumulation of ␥H2AX without 53BP1 colocalization at S phase, which could represent unresolved replication-fork stalling caused by DNA damages (39). These findings indicated that S phase ICL repair requires Rev7 and suggest that DNA Pol functions downstream of the FA pathway.…”
Section: Similar To Cells With the Rev7mentioning
confidence: 70%
“…HNE Treatment Induces Phosphorylation of Histone H2A.X at Ser-139-Because HNE causes DNA damage, we examined whether HNE treatment caused DNA double strand breaks by monitoring Ser-139 phosphorylation of H2A.X, which is a sensitive marker for the presence of DNA double strand breaks (52)(53)(54). Western blot studies clearly showed a concentrationdependent phosphorylation of H2A.X in HNE-treated HepG2 and Hep3B (Fig.…”
Section: Hne Induces Phosphorylation Of Atr and Chk1mentioning
confidence: 92%